Case Report: Coil Occlusion of Two Congenital Coronary Cameral Fistulas Connecting Right and Left Circumflex Arteries to the Right Ventricle: An Innovative Stent-Assisted Technique - Buzaev, Igor V.; Plechev, Vladimir V.; Khalikova, Gulchachak; Khabirova, Kristina; Nikolaeva, Irina Evgenievna; Onorato, Eustaquio Maria (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary cameral fistulas (CCFs) are rare congenital malformations consisting of abnormal vascular connections between coronary arteries and cardiac chambers, often incidentally found during cardiac catheterizations. Case summary A 66-year-old female asymptomatic patient, without cardiovascular risk factors and a history of varicose veins lower extremities and coronavirus disease 2019 (COVID-19) pneumonia in December 2020, was diagnosed by coronary angiography with two large coronary cameral fistulas connecting the distal right coronary artery (RCA) and the distal left circumflex artery (LCx) to the right ventricle (RV). Additional imaging modalities such as two-dimensional transthoracic/transesophageal echocardiography and three-dimensional multidetector CT angiography were required to confirm the fistula's pathway (location, number, and size), which was difficult to delineate using selective coronary angiography alone. After heart team discussion, with the aim to reduce the risk of embolization, an innovative stent-assisted coil occlusion antegrade technique was used with optimal immediate results. Discussion Even though our otherwise asymptomatic patient was not the best suitable candidate for an interventional procedure (large vessels, multiple fistulas without distal narrowing, distal portion of the fistula not accessible with the closure device), the innovative stent-assisted fistula coil occlusion technique to stabilize the first coil and deploy safely the additional ones resulted to be key for successful and complete obliteration of the abnormal congenital vascular connections.